Profil Kasus Tuberkulosis Resisten Obat di RSUP Dr. Soeradji Tirtonegoro Klaten Periode Tahun 2012-2017 - Alifia Rimadhani Yuwono; Surya Amal; Lija Oktya Artanti (University Of Darussalam Gontor, 2018)
DR TB (Drug Resistance Tuberculosis) is the resistance of Micobacterium tuberculosis to anti-tuberculosis drugs. These study aims are to observe and identify the case profile of drug-resistant tuberculosis, which includes patient characteristics and resistance patterns of Micobacterium tuberculosis against ATD at dr. Soeradji Tirtonegoro Klaten. The type of research is descriptive-retrospective based on secondary data from laboratory data and medical records in the period 2012-2017. Sampling was done by total sampling technique. Obtained a total population of TB patients resistant was 15 patients with 10 patients who met the inclusion criteria expressed in the study sample. Characteristics of patients with drug-resistant tuberculosis, mostly found were female (60%) with an age range of 60-70 years (40%). Mostly origins of Klaten (central region) (90%). The educational status was high school graduated (50%), not working (60%), comorbidities were bronchiectasis (15.4%), the nutritional status was underweight (60%), and suffering the pulmonary TB (70%). The result of this study showed the resistance patterns were primary resistance (50%) and secondary resistance (50%). Resistant to 1 ATD (60%), 2 ATD (30%), 3 ATD (10%). The highest resistance was monoresistant streptomycin (20%), ethambutol (20%), rifampicin (10%), Isoniazid(10%). Polyresistant found was the combination of ethambutol and streptomycin (30%). MDR TB incidence (10%) was the combination of rifampicin + ethambutol + streptomycin. The highest sensitivity